Strain facilitated small gas molecules sensing properties on Au doped SnSe2 monolayer. (12th April 2022) - Lin, Long; Pang, Donglin; Shi, Pei; Yan, Longbin; Lou, Mengsi; Chen, Ruixin; Chen, Yujin; Wang, Yanfang; Zhang, Zhanying
Abstract: By the first-principles calculations, the sensitivity of CO, H2 O and NO adsorption on Au doped SnSe2 monolayer surface is investigated. The results show that CO and H2 O molecules are physically adsorbed on Au doped SnSe2 monolayer and act as donors to transfer 0.012 e and 0.044 e to the substrate, respectively. However, the NO molecule is chemically adsorbed on substrate and acts as an acceptor to obtain 0.116 e from the substrate. In addition, our results also show that the biaxial strain can effectively improve the adsorption energy and charge transfer of gas molecules adsorbed on the substrate surface. Also, the recovery time of desorbed gas molecules on the substrate surface is calculated, and the results indicate that the Au doped SnSe2 is a perfect sensing material for detection and recovery of CO and NO under −8% strain. Highlights: The sensitivity of CO, H2 O and NO gas molecules to Au doped SnSe2 monolayer was studied by the first-principles method. The adsorption stability of gas molecules CO, H2 O and NO on the Au doped SnSe2 surface was enhanced in turn. The biaxial strain can effectively improve the adsorption performance of three gas molecules on the Au doped SnSe2 surface. The recovery time of desorbed gas molecules on the Au doped SnSe2 surface was calculated. The Au doped SnSe2 monolayer may be an ideal sensing material for detecting CO and NO molecules.